OPTIMIZATION OF LIGHTING INTENSITY IN BATAM PUBLIC LIBRARY READING ROOM - Yovita Yolanda Budiman; Stivani Ayuning Suwarlan (Journal of Architectural Research and Education, 2023)
Lighting is one of the most critical components that support human life and other living creature. Poor illumination can impede users’ ability to use a building or space effectively. Library is one of the places that require good light spread so that users feel comfortable when doing activities in it. The Batam City public library is a library located on the fourth floor of the Batam City joint office. This library only has four small apertures in the form of windows for a 13.2 meter x 9 meter area, therefore sunlight cannot distribute evenly. Therefore, one solution to ensure that the library room has a suitable distribution of light is to employ artificial lighting. According to a questionnaire distributed to visitors and staff of Batam City public libraries, 82.4% of respondents believed that lighting in Batam City public libraries was still inadequate. This study used data from direct field observations, interviews with staff and library visitors, questionnaire distribution, and literature review. This research uses quantitative methods by calculating light intensity through the simulation of dialux software. Simulations were carried out in the catalogue room and the library reading room. Changing the colour of the wall surface, the furniture arrangement and the lights' placement are some experiments done to provide a good distribution of light. This study aims to evaluate and obtain lighting simulation results for the public library in Batam City that adheres to the SNI standard (300 LUX).